Modern approaches to herbal preparations efficacy and safety assessment in Russia and abroad - E. I. Sakanyan; T. B. Shemeryankina; Yu. K. Malkina; M. N. Lyakina; N. A. Postoyuk (Регуляторные исследования и экспертиза лекарственных средств)
For the purpose of prevention and treatment of various diseases, herbal medicinal products are used along with a wide range of small molecule drugs. Herewith herbal preparations are not only herbs and combined herbal products, but also various galenic and new galenic preparations and individual biologically active compounds derived from plants. The growth of demand for herbal medicinal product, the changing requirements of the regulatory system to their safety and effectiveness during the procedure of registration puts certain tasks to improve this procedure. The article provides an overview of the literature data on contemporary requirements for safety and efficacy assessment of herbal preparations. Analysis of approaches to conducting preclinical and clinical studies of herbal preparations in Russia and the international community led to certain conclusions on the degree of their harmonization and possible unification.